Penerapan Lean Manufacturing Untuk Mengurangi Waste Pada Cat Tanki Dengan Metode WRM dan WAQ - Edi Prasetyo, Eko Setiawan; Suryatman, Tina Hernawati (Journal Industrial Manufacturing, 2023)
In the fabrication process always maintain and improve the quality and capacity of the company, but in the fabrication process there are several obstacles that affect product delivery to the project. Because the achievement of the productivity of the company PT Prakarsa Langgeng Maju Bersama is less than optimal because there is still a lot of waste (waste) in the fabrication process. The waste contained in the fabrication process is motion waste, inventory waste, defect waste. Based on the data obtained, there are 245 hours of excess work. For this reason, waste is carried out using a Lean Manufacturing approach, namely the WRM Waste Relationship Matrix and WAQ Waste Assessment Questionnaire by 5W + 1H which is used to support waste and also to find out the relationship between the seven wastes so that existing waste can be eliminated. the highest was Motion at 25.4%, followed by Inventory at 18.4%. and Disability by 15.1%. Proposed improvements related to productivity, need SOPs in machine setup, standardize all processes and inventory management, provide control training to the workers concerned, improve coordination between departments, make tools to standardize all processes and Poka yoke, increase work motivation, improved supervision and implementation of Poka Yoke.Keywords: Lean Manufacturing, Waste Relationship Matrix, Waste Assesment Quesioner, Fishbone Diagram, Poka Yoke